Conceptual aspects of management of the distribution of medical supplies from the position of military pharmaceutical logistics - M. V. Bilous; O. P. Shmatenko; O. A. Ryzhov; V. V. Trokhymchuk; О. V. Galan; D. V. Drozdov (The State Expert Center of the Ministry of Health of Ukraine, 2019)
One of the main directions of logistic support of the Armed Forces of Ukraine is medical support which is aimed at life safeguard and health of military personnel, well-timed and efficient provision of medical care in the event of injuries, injuries and diseases, fast renewal of combat power and ability to work in different conditions of its handling and at different period of time. The readiness of medical service of the Armed Forces of Ukraine to the medical support of the troops depends on the well-timed organization of medical supplies and the refilling of medical supplies full and complete. The qualitative and efficient allocation of medical equipment and medical supplies is a determining factor in this process. The aim of the work - reasoning of the irregularity of distribution logistics in the unified logistic system of the Armed Forces of Ukraine and the study of the main aspects of management of the distribution of medical supplies from the position of military pharmaceutical logistics. To get the purpose of the research, the analysis of domestic scientific sources and the current normative and legal base of Ukraine have been carried out. Research methods are: information search, comparison, systemization, semantic analysis, synthesis and modeling. In the conditions of logistic support of the Armed Forces of Ukraine and other components of the security and defense forces of Ukraine, the logistic function of the distribution of logistical equipment, inventory, military equipment and services (food, bath and laundry services, etc.) should ensure the activity of troops (forces) in peacetime and war time. It is the guarantee of the ability to ensure the defense of the state and appropriate response to military threats to the national security of Ukraine, efficiently using available potential and resources. Distribution logistics from the position of military pharmaceutical logistics is the management of all functional subsystems of the medical supplies and health services of the Ministry of Defense of Ukraine in order to optimize the distribution of the material flow (purchased medical supplies) from the supplier to the final consumer (according to the applications of the Military Medical Clinical Centers of the Regions). Same, distributive logistics in the structure of a unified logistic support system of the Armed Forces of Ukraine does not carry a commercial component, and its functions consist in planning, organization of distribution, control and regulation of the logistic process of distribution of material and technical means (including medical equipment and supplies), inventory, military equipment, services (catering, bath and laundry service, etc.). According to the authors, the term «marketing logistics» is not possible to use as a single system of logistic support of the Armed Forces of Ukraine, and in its subsystems. To sum it up, it was suggested to use the term «distributive logistics». On the basis of theoretical generalization of the data of scientific literature and normative legal acts, the main aspects of management of the distribution of medical equipment and supplies from the standpoint of military pharmaceutical logistics are studied. The functions of distributive logistics are defined, the model of the current logistic chain of distribution of medical equipment and supplies in the medical service of the Armed Forces of Ukraine is constructed. It is noted that in order to ensure the qualitative and efficient distribution of medical equipment and supplies, a regulatory and legal framework which regulates the division of powers between institutions and units of medical supplies and defines the responsibility for their implementation in the current conditions of the reformation of the Armed Forces of Ukraine.